"I put diabetes on the shelf": African-American Women's Perceptions of Risk for Diabetes Complications. (September 2021) - Ochieng, Judith Muhonja; Crist, Janice D.
The purpose of this study was to describe the perceptions of African American (AA) women with Type 2 diabetes mellitus (T2DM) about developing diabetes mellitus (DM) complications and explore how their perceived risk influenced DM self-management. Ten ( N  = 10) AA women participated in the qualitative description study through semi-structured interviews. Thematic analysis informed by the Health Belief Model and Risk Perception Conceptual Model revealed the perceived probability of DM complications by AA women with T2DM and how they made judgments regarding the seriousness, extent, or severity of complications. Those with high levels of DM knowledge perceived themselves at high risk of developing DM complications and those with low DM knowledge perceived themselves at low risk of DM complications. Risk perceptions and health literacy also influenced DM self-management behaviors.